Co nowego w alergologii kontaktowej? - Kieć-Świerczyńska, Marta (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Allergic contact dermatitis is a frequent, chronic skin disease, mainly of occupational origin. It affects younger and younger individuals, involves some economic costs and causes a decrease in quality of life. In the nineteen seventies and eighties the distribution of contact allergy in Poland was significantly different in comparison with Western Europe. The most frequent allergens were chromates, aromatic amines, turpentine and epoxy resins, while the frequency of sensitization to nickel, acrylic plastics and neomycin was lower than in other European countries. At present, there are only slight differences in occurrence of contact allergy between Poland and Western Europe. Recent observations pointed out changes in frequency of contact allergy to metals, rubber, fragrances, cosmetic preservatives and 4-phenylenediamine. Metals. In Denmark and Germany, since the “Nickel Directive” came into force, a decrease in frequency of nickel allergy has been noted. We have not observed such a tendency in our centre yet. Metal implants used in orthopaedic and cardiovascular surgery are considered as possible sources of sensitization to metals. A rising problem is to identify sources of allergy to chromates. Rubber. A decrease in sensitization to rubber of medical gloves is a result of changes in technology of glove production. Fragrances. The frequency of allergy to fragrances continuously increases. At the same time alterations in distribution of hypersensitivity to particular fragrances are observed, especially an increase in allergy to Lyral. Cosmetic preservatives. New alternative cosmetic preservatives turned out to have comparable or stronger allergenic properties than former ones. That is why there is no decreasing tendency in sensitization to preservatives. 4-Phenylenediamine. An increase in contact allergy to paraphenylenediamine has been caused by more frequent hair dying and skin tattooing by women and men. Because of changes in frequency and distribution of contact allergy it is necessary to follow the development of new technologies in industry and work out effective preventive strategies.